Software Process Improvement and Capability Determination 14th International Conference, SPICE 2014, Vilnius, Lithuania, November 4-6, 2014, Proceedings - Mitasiunas, Antanas; Rout, Terry; O$1 (BConnor, Rory V.s; Dorling, Alec.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book constitutes the refereed proceedings of the 14th International Conference on Software Process Improvement and Capability Determination, SPICE 2014, held in Vilnius, Lithuania, in November 2014. The 21 revised full papers presented together with 6 short papers were carefully reviewed and selected from 49 submissions. The papers are organized in topical sections on developing process models for assessment; software process and models; software models and product lines; assessment; agile processes; processes improvement and VSE.
Developing process models for assessment -- Software process and models -- Software models and product lines -- Assessment -- Agile processes -- Processes improvement and VSE.
Keywords: Computer science; Information technology; Business -- Data processing; Software engineering; Application software; Management information systems; Computer Science; Management of Computing and Information Systems; Software Engineering; IT in Business; Computer Appl. in Administrative Data Processing; Electronic books